Client/server over ATM making use of broadband to support client/server applications - Minoli, Daniel 1952- (MANNING, 1996)
Today, to meet the surging demands of client/server company-wide processes - distributed cooperative computing, business/scientific imaging, video conferencing, multimedia, distance learning and many more - corporations are finding they must extend high-speed communications beyond just a few key sites. This book discusses ATM as the key technology for transforming the enterprise network from data-only to an integrated data, voice, video, image and multimedia corporate infrastructure. Previous books have covered ATM and client/server separately. This book, intended for networking professionals, is unique in its focus on the hows and whys of the inevitable marriage of these two technologies.